Brand Repositioning and Diversity: A Case Study of Lucky Dube - Willie, Michael Mncedisi (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study examines Lucky Dube’s brand repositioning from Mbaqanga to reggae, highlighting how it expanded his global reach while preserving his African identity. Research Design and Methodology: A qualitative approach, including a literature review and case studies, applies branding theories such as cultural branding and Aaker’s Brand Equity Model to assess Dube’s market expansion. Findings and Discussion: Key factors in Dube’s success include authenticity, audience engagement, and strategic communication, demonstrating how artists can broaden their appeal while maintaining cultural identity. Implications: The study offers branding insights applicable across industries, emphasizing authenticity, targeted engagement, and strategic communication to strengthen brand equity.